Virus‐induced gene silencing as a tool for functional studies in Cleome violacea. (14th June 2021) - Carey, Shane; Higuera‐Díaz, Mónica; Mankowski, Peter; Rocca, Alexandra; Hall, Jocelyn C.
Abstract : Premise: Cleomaceae is emerging as a promising family to investigate a wide range of phenomena, such as C4 photosynthesis and floral diversity. However, functional techniques are lacking for elucidating this diversity. Herein, we establish virus‐induced gene silencing (VIGS) as a method of generating functional data for Cleome violacea, bolstering Cleomaceae as a model system. Methods: We leveraged the sister relationship of Cleomaceae and Brassicaceae by using constructs readily available for Arabidopsis thaliana to provide initial information about the feasibility of VIGS in C . violacea . We then developed endogenous constructs to optimize VIGS efficiency and viability for fruit development. Results: PHYTOENE DESATURASE was successfully downregulated in C . violacea using both heterologous and endogenous constructs. The endogenous construct had the highest degree of downregulation, with many plants displaying strong photobleaching. FRUITFULL ‐treated plants were also successfully downregulated, with a high rate of survival but less effective silencing; only a small percentage of survivors showed a strong phenotype. Discussion: Our optimized VIGS protocol in C . violacea enables functional gene analyses at different developmental stages. Additionally, C . violacea is amenable to heterologous knockdown, which suggests that a first pass using non‐endogenous constructs is a possible route to test additional species of Cleomaceae.